Low Contrast Image Enhancement Based On Undecimated Wavelet Transform with SSR - Naik, Namita; Mishra, Agya (International Journal of Computer Sciences and Engineering, 2025)
Image Enhancement refers to accentuation or sharpening of image features such as edges, boundaries or contrast so as to get finer details of an image. In this paper a low contrast image enhancement algorithm using Single Scale Retinex (SSR) with undecimated wavelet transform (UWT) has been proposed. The performance of the proposed algorithm is evaluated using a statistical visual contrast measure (VCM). Experimental results obtained from the proposed algorithm gives improvement in terms of the VCM. Paper concludes comparison with existing algorithm and shows that the proposed method performs quite efficiently.